2016
DOI: 10.1007/s00380-016-0858-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum carboxy-terminal telopeptide of type I collagen (I-CTP) is predictive of clinical outcome in peripheral artery disease patients following endovascular therapy

Abstract: Peripheral artery disease (PAD) is a risk factor for the development of heart failure and mortality. The serum levels of carboxy-terminal telopeptide of type I collagen (I-CTP), a marker for collagen degradation derived from the extracellular matrix of vascular and myocardial tissue, is reportedly a useful marker for cardiac events in patients with heart disease. However, it remains unclear whether I-CTP can predict poor clinical outcome in patients with PAD. Serum I-CTP was measured in 246 consecutive PAD pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
0
10
0
6
Order By: Relevance
“…The 47 included studies were sorted per biomarker; several studies appeared in different groups as they investigated multiple biomarkers. The following biomarkers were studied: 13 studies investigated high-sensitivity CRP (hs-CRP), 11 , 14 26 2 reported on GDF-15 (growth differentiation factor 15), 14 , 27 2 on MPO (myeloperoxidase), 24 , 28 6 on the neutrophil-lymphocyte ratio (NLR), 29 34 2 assessed SAA (serum amyloid A), 22 , 35 6 reported on fibrinogen, 19 , 35 39 another 7 assessed d -dimer, 22 , 25 , 38 , 40 43 7 investigated NT-proBNP, 11 , 15 , 17 , 44 47 5 hs-cTnT, 10 , 44 , 45 , 48 , 49 4 asymmetrical dimethylarginine (ADMA), 50 53 4 assessed adiponectin, 54 57 and 3 homocysteine. 18 , 22 , 58 Investigated outcomes were heterogenous across studies but mainly included all-cause mortality, cardiovascular mortality, cardiovascular events, major adverse cardiovascular events (MACE), major adverse limb events, coronary events, amputation-free survival, amputation, reintervention for lower extremity PAD, and graft patency.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 47 included studies were sorted per biomarker; several studies appeared in different groups as they investigated multiple biomarkers. The following biomarkers were studied: 13 studies investigated high-sensitivity CRP (hs-CRP), 11 , 14 26 2 reported on GDF-15 (growth differentiation factor 15), 14 , 27 2 on MPO (myeloperoxidase), 24 , 28 6 on the neutrophil-lymphocyte ratio (NLR), 29 34 2 assessed SAA (serum amyloid A), 22 , 35 6 reported on fibrinogen, 19 , 35 39 another 7 assessed d -dimer, 22 , 25 , 38 , 40 43 7 investigated NT-proBNP, 11 , 15 , 17 , 44 47 5 hs-cTnT, 10 , 44 , 45 , 48 , 49 4 asymmetrical dimethylarginine (ADMA), 50 53 4 assessed adiponectin, 54 57 and 3 homocysteine. 18 , 22 , 58 Investigated outcomes were heterogenous across studies but mainly included all-cause mortality, cardiovascular mortality, cardiovascular events, major adverse cardiovascular events (MACE), major adverse limb events, coronary events, amputation-free survival, amputation, reintervention for lower extremity PAD, and graft patency.…”
Section: Resultsmentioning
confidence: 99%
“…The 18 articles that were not selected studied α-defensin, 21 matrix metalloproteinase 10, 59 galectin-3, 60 soluble tumor necrosis–like weak inducer of apoptosis, 61 ferritin, 62 activated protein C–protein C inhibitor complex, 63 angiopoietin-related growth factor, 64 fatty acid–binding protein 4, 65 alkyl-phosphatidylcholine and alkenylphosphatidylcholine lipids, 66 high-density lipoprotein cholesterol, 66 malondialdehyde-modified low-density lipoprotein, 67 lipoprotein-associated phospholipase A2, 68 cardiac troponin I, 69 phosphate, 70 carboxy-terminal telopeptide of type I collagen, 15 cholinesterase, 71 eicosapentaenoic acid/arachidonic acid ratio, 72 or endothelin-1. 73 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, preliminary clinical studies of atherosclerosis markers MMP‐mediated collagen type I degradation (C1M), MMP‐mediated degradation of collagen type IV (C4M) and MMP‐mediated degradation of laminin (LG1M) shown to be associated with cardiovascular events, acute myocardial infarction and cardiovascular death . Carboxyterminal telopeptide of collagen type I (CITP) and collagen type III turnover (PIIINP) has also shown to be associated with various cardiovascular outcomes and mortality in well‐known studies, such as the Framingham study . Furthermore, MMP‐12 has been showed to predict coronary events .…”
Section: Neo‐epitope Biomarkers For Atherosclerosis Generated From Ecmentioning
confidence: 99%
“…Despite advances in endovascular therapy (EVT), PAD remains an important medical issue with an increasing prevalence and high all-cause and cardiovascular mortality rates. [1][2][3][4] Therefore, identifying patients with PAD at an early stage is increasingly important. Further, high-risk patients with PAD should be stratified according to risk.…”
Section: Subjectsmentioning
confidence: 99%